CYBERBULLYING DARI ASPEK KRIMINOLOGI - Imas Octaviana Dewi; Lalu Parman; Ufran Ufran (Legalitas: Jurnal Hukum, 2022)
This study aims to identify and analyze the modus operandi of cyberbullying and to analyze methods of overcoming cyberbullying. The method in this study is a normative research method using a conceptual approach, legislation, case approach. The results of this study include: The modus operandi of cyberbullying can be divided into several parts, namely: Exclusion, Flaming, Impersonation, Trickery, Fraping, Dissing, Cyberstalking (mental attack). Methods of overcoming cyberbullying can be done penal and non-penal. The method of overcoming through penal means in general can be identified through the Criminal Code (KUHP) in Articles 310, 311 and 315 of the Criminal Code. Meanwhile, it is specifically regulated in Law Number 19 of 2016 concerning Amendments to Law Number I1 of 2008 concerning Information and Electronic Transactions in Article 27 (paragraph 1), 3), 4), Article 28 paragraph 2), and Article 29 The criminal provisions of these articles are regulated in CHAPTER XI concerning criminal provisions in Law Number I1 of 2008 concerning Information and Electronic Transactions. Non-penally, overcoming cyberbullying consists of several parts, namely: a cultural approach, a moral approach, a scientific approach, and a technology approach.